Bone and lean mass inter-arm asymmetries in young male tennis players depend on training frequency - Sanchis-Moysi, J.; Dorado, C.; Olmedillas, H.; Serrano-Sanchez, J. A.; Calbet, J. A. L. (European Journal of Applied Physiology, 2010)
Professional tennis players (TP) have marked inter-arm asymmetry in bone mass (BMC) and density (BMD). To determine if this asymmetry is influenced by training frequency and volume, we studied 24 young tennis players (mean age 10.6 years, Tanner 1-2), 17 physically active control boys (CG) and ten male professional tennis players. Young TP were divided into two groups depending on the number of training days per week (TP5: 5 days/week, n = 10; TP2: 2 days/week, n = 14). In young TP, the dominant arm (DA) compared to the non-dominant arm (NDA) had greater lean mass (TP5, 13.3 ± 2.0% and TP2, 8.3 ± 1.3%), BMC (TP5, 22.4 ± 4.1% and TP2, 12.1 ± 2.2%), bone area (TP5, 15.6 ± 3.3% and TP2, 7.9 ± 2.2%) and BMD (TP5, 4.6 ± 1.5% and TP2, 3.8± 0.6%). Inter-arm asymmetry in lean mass, BMC and bone area was greater in TP5 than TP2, being related to the number of weekly hours devoted to tennis (r = 0.45-52, P < 0.05). No significant differences in lumbar spine or femoral neck BMC or BMD were observed between TP5, TP2 and CG. In professional TP, the DA had 18, 32, 11 and 15% greater lean mass, BMC, bone area and BMD than the NDA. Thus, TP5 had 69% of the inter-arm asymmetry in BMC observed in professional TP and a similar inter-arm asymmetry in bone area, although this comparison may not be generalisable. Young tennis players have increased BMC, bone area and lean mass in dominant arm, which magnitude depends on the number of weekly hours devoted to tennis.